The Effects of Rural Youth Outmigration on Migrant-sending Households in Gojjam and Wolayta, Ethiopia - Mekonnen, Teferi (Ethiopian Journal of Social Sciences, 2018)
Rural youth outmigration from densely populated agricultural areas is a common phenomenon in Ethiopia. The purpose of this study is to assess the impacts of youth outmigration on the socioeconomic and demographic behavior of migrant-sending households using survey data and in-depth interviews. The findings revealed that remittances are considered important by the migrant-sending households to enhance asset formation, increase levels of income and consumption, improve debt repayment position, and augment family member’s education and medication expenses. The study further underscored the positive impacts of youth rural outmigration in improving human-environment relations through fertility reduction and easing population pressure, and mitigation of harmful traditional practices.